2019
DOI: 10.1002/elps.201900259
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity profiling of anthracycline antibiotics by microemulsion electrokinetic chromatography–effects on cardiotoxicity and endotheliotoxicity

Abstract: Accurate profiling of the lipophilicity of amphoteric compounds might be complex and laborious. In the present work the lipophilicity of 12 anthracycline antibiotics–four parent drugs: doxorubicin, daunorubicin, epidoxorubicin, and epidaunorubicin and eight novel formamidyne derivatives with attached morpholine, hexamethylenoimine or piperidine rings–was determined based on novel approach using MEEKC. In the second stage, lipophilicity was correlated with anthracycline toxicity towards two cell lines. In rat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The lipophilic ability could be an underlying factor that leads to the differences in protein profiles, in which IDA has higher lipophilicity than its parent molecule, daunorubicin ( Matyszewska, 2020 ), while daunorubicin has higher lipophilicity than DOX ( Matyjaszczyk-Gwarda et al, 2019 ). Specially, a rat cardiomyoblast study showed the inverse correlation between the lipophilicity of ANT analogs and their toxicity ( Matyjaszczyk-Gwarda et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lipophilic ability could be an underlying factor that leads to the differences in protein profiles, in which IDA has higher lipophilicity than its parent molecule, daunorubicin ( Matyszewska, 2020 ), while daunorubicin has higher lipophilicity than DOX ( Matyjaszczyk-Gwarda et al, 2019 ). Specially, a rat cardiomyoblast study showed the inverse correlation between the lipophilicity of ANT analogs and their toxicity ( Matyjaszczyk-Gwarda et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lipophilic ability could be an underlying factor that leads to the differences in protein profiles, in which IDA has higher lipophilicity than its parent molecule, daunorubicin [77], while daunorubicin has higher lipophilicity than DOX [78]. Interestingly, a rat cardiomyoblast study showed the inverse correlation between the lipophilicity of ANT analogs and their toxicity [78].…”
Section: Discussionmentioning
confidence: 99%